PHYSICAL DEVELOPMENT OF PERM INFANTS - I. G. Biyanova; N. B. Merzlova; A. N. Biyanov ("Paediatrician" Publishers LLC, 2013)
The authors analyze the indicators of physical development (body weight, body length, chest circumference) of Perm infants at the age from birth to 3 years old and show the rational percentile charts for the physical development of children at the age up for 3 years old assessment. The comparative analysis of physical development of infants in dynamics with the results of 1968 and 2008 examinations was performed. It was established that at present time the body length of infants at the age up for 3 years and the body weight of the infants at the age up for 6 months are higher than these characteristics at 1968.